(untitled) (Bangladesh Journal of Microbiology, 2019)
The present study was undertaken to observe the transmission of microbial contaminants through different electronic devices. Five different bacteria such as Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas spp. and Bacillus spp. were cultivated from the surface of 50 different automated teller machines (ATMs) of 10 different banks located in Dhaka City. Among them, the number of Pseudomonas spp. and S. epidermidis were found up to 104 cfu/ml while the S. aureus was quantified up to 106 cfu/ml. Fungal contamination was also observed in all cases within the range of 104 and 105cfu/ml. Most of the isolates were found to be resistant against more than one antibiotic. Only Streptomycin and Gentamicin were found to be effective against all the bacteria. Out of 50 strains (coagulase positive) of S. aureus, 40 (80%) were found as Oxacillin and Methicillin resistant. Among 40 MRSA strains, 25 (62.5%) were found to be resistant against vancomycin which is referred to as VRSA. The isolated MDR bacteria from the surface of the ATM may be a health concern for the users Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 23-27